2012
DOI: 10.1371/journal.pone.0041629
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNAs, miR-223, miR-21 and miR-218, as Novel Potential Biomarkers for Gastric Cancer Detection

Abstract: BackgroundMicroRNAs (miRNAs), endogenous small non-coding RNAs, are stably detected in human plasma. Early diagnosis of gastric cancer (GC) is very important to improve the therapy effect and prolong the survival of patients. We aimed to identify whether four miRNAs (miR-223, miR-21, miR-218 and miR-25) closely associated with the tumorigenesis or metastasis of GC can serve as novel potential biomarkers for GC detection.MethodologyWe initially measured the plasma levels of the four miRNAs in 10 GC patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(158 citation statements)
references
References 35 publications
6
151
1
Order By: Relevance
“…Although many studies have reported the close relationship between plasma miRNAs and cancer, one plasma miRNA has been shown to be altered in multiple types of cancers [e.g. changes in miR-21 in the plasma can potentially indicate colorectal cancer (134) and gastric cancer (135)], which makes the diagnostic value lower than the four materials we listed previously. We did not put much emphasis on the blood biomarker limitations we discussed (low sensitivity, scarce quantity, complex nature and lack of reproducibility).…”
Section: Conclusion and Prospectsmentioning
confidence: 90%
“…Although many studies have reported the close relationship between plasma miRNAs and cancer, one plasma miRNA has been shown to be altered in multiple types of cancers [e.g. changes in miR-21 in the plasma can potentially indicate colorectal cancer (134) and gastric cancer (135)], which makes the diagnostic value lower than the four materials we listed previously. We did not put much emphasis on the blood biomarker limitations we discussed (low sensitivity, scarce quantity, complex nature and lack of reproducibility).…”
Section: Conclusion and Prospectsmentioning
confidence: 90%
“…To determine the relationship between miR-491 and malignant potential, we used HepG2 and MHCC97H cell lines for knockdown and overexpression of miR-491, respectively. miRNAs have the capacity to inhibit translation and to induce mRNA degradation, predominantly through targeting of the 3′-UTRs of mRNAs [31]. In ovarian carcinomas, miR-491-5p binds to the EGFR 3′-UTR to mediate a repressive effect on protein expression [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that miR-218 is downregulated in various types of cancer, including cervical cancer, gastric cancer, lung cancer, colon cancer, prostate cancer, and bladder cancer (Davidson et al, 2010;Song et al, 2010;Tie et al, 2010;Leite et al, 2011;Uesugi et al, 2011;Li et al, 2012a;Li et al, 2012b;Chiyomaru et al, 2012;He et al, 2012). However, the level of miR0218 expression, and its clinical significance in pancreatic cancer, remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%